2018
DOI: 10.11606/s1518-8787.2018052000109
|View full text |Cite
|
Sign up to set email alerts
|

Intervenções educativas em serviços de saúde e saúde bucal: revisão sistemática

Abstract: OBJECTIVETo analyze the effectiveness of educational interventions performed in health services in the improvement of clinical behaviors and outcomes in oral health.METHODSWe have carried out a systematic review of the literature searching the PubMed, Lilacs, and SciELO databases. We have included studies that have investigated interventions performed by health professionals working in health services and who have used educational actions as main approach to improve behavioral and clinical outcomes in oral hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
20

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 51 publications
(105 reference statements)
2
29
0
20
Order By: Relevance
“…Oral diseases are among the most prevalent diseases worldwide and produce abundant health and economic burdens, reducing quality of life for individuals and societies affected [1]. Health education is considered one of the fundamental elements in the success of disease prevention in several areas of health care, including oral and dental health [2]. Among the most reliable methods of oral health education, the attitudes and behaviour of oral health providers towards their own dental and oral hygiene can have a major impact on improving public oral health [3].…”
Section: Introductionmentioning
confidence: 99%
“…Oral diseases are among the most prevalent diseases worldwide and produce abundant health and economic burdens, reducing quality of life for individuals and societies affected [1]. Health education is considered one of the fundamental elements in the success of disease prevention in several areas of health care, including oral and dental health [2]. Among the most reliable methods of oral health education, the attitudes and behaviour of oral health providers towards their own dental and oral hygiene can have a major impact on improving public oral health [3].…”
Section: Introductionmentioning
confidence: 99%
“…Future studies should focus on the long-term effects of this oral health promotion program on the elderly's oral health status and behaviors, as most of the studies have a duration of study <2 years. [222324] Furthermore, evidence from this study suggests that health workers should be trained, both informal and formal,[2526] to apply appropriate oral health promotion including continuing re-enforcement. To confirm the success of the program as recommended by the WHO,[27] extensive community engagement to enhance ownership of the program is needed, whereas the Ministry of Health should have policy and funding to support the promotion program among local health service organizations.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study may be included in the short-term effects. Menegaz et al suggested that a follow-up time of less than one year led to a lack of efficacy for educational intervention [23]. In addition, Oshikohji et al reported that workers who had more participation time for oral examination and oral health instruction had better periodontal condition than those with less time [24].…”
Section: Discussionmentioning
confidence: 99%